Growth in Telehealth Use in Bangladesh from 2019-2021 - A Difference-in-Differences Approach - Rahman, Saanjaana; Amit, Sajid (Journal of Medicine, 2022)
Purpose of the ProjectTo examine the change in telehealth use growth during the COVID-19pandemic with non-elderly patients in Bangladesh. Methods Using patients of age between 18-64 from residents in and outside Dhaka, this study analyzedtelehealth visits, and all health care procedures from 2019-2021. The inflection point of interest wasMarch 2020, the month when the COVID-19 pandemic was officially declared as a national emergency.Analyses were controlled for age, gender, and socioeconomic index. We used DiD approach to see thegrowth in telehealth use and then performed logistic regression to evaluate the association between anytelehealth use and patient characteristics. Results There were more than 3000 observations in the analysis, where more than 60% were female.The percentage of females did not decrease after the inflection point. The onset of the pandemic wasassociated with an increase in telehealth usage in Dhaka relative to outside Dhaka (DiD estimate 0.07;95% CI, -0.77-0.62). The mean telehealth visits in Dhaka after March 2020 was 33% higher than outsideDhaka per person-year. The mean (SD) of Dhaka and outside Dhaka were 1.69 (7.03) and 1.48 (7.62)respectively.Interpretations Overall, telehealth use was associated with the youngest age group of 18-34, living inmore urban areas and living in areas of higher socioeconomic status. Conclusion In this study, we found a significant decrease to in-person services and a rise in telehealthvisits. J MEDICINE 2022; 23: 42-47